7-х=6х+11 4*(2х+11)-5х=7х+-(х-8) 2*(х-9)=15*(х-3) 6*(3х+8)-(х-5)=2х+11 3*(х-5)-4*(2-х)=6...

0 голосов
38 просмотров

7-х=6х+11
4*(2х+11)-5х=7х+-(х-8)
2*(х-9)=15*(х-3)
6*(3х+8)-(х-5)=2х+11
3*(х-5)-4*(2-х)=6
(х-3)-(х+8)=7х-12 помогите пж срочно нужно


Алгебра (85 баллов) | 38 просмотров
Дан 1 ответ
0 голосов

1) 7 - x = 6x + 11
- x - 6x = 11 - 7
-7x = 4     x = - 4/7
2) 4*(2x + 11) - 5x = 7x + (x - 8)
8x + 44 - 5x = 7x + x - 8
3x - 8x = -8 - 44
- 5x = - 52       x = 10,4
3)2*(x - 9) = 15*(x - 3)
2x - 18 = 15x - 45
- 13x = - 27      x = (2)1/13
4)6*(3x + 8) - (x - 5) = 2x + 11
18x + 48 - x + 5 = 2x + 11
15x = - 42     x = - 2,8
5)3*(x - 5) - 4*(2 - x)= 6
3x - 15 - 8 + 4x = 6
7x = 29    x = (4)1/7
6) (x - 3) - (x - 8) = 7x - 12
x - 3 - x + 8 = 7x - 12
- 7x = - 17    x = (2)3/7


(220k баллов)
0

спасибо огромное